Model DFIG Pembangkit Listrik Tenaga Angin Sebagai Suatu Unit Pembangkit Tersebar - Ramadoni Syahputra; Imam Robandi; Mochamad Ashari (FT- UNDAR, 2017)
In this paper, we present the doubly-fed induction generator (DFIG) model in a wind turbine system as a unit of the distributed generator. The wind turbine driven by doubly-fed induction machine is a part of the distributed generation which feeds ac power to the distribution network. The system is modeled and simulated in the Matlab Simulink environment in such a way that it can be suited for modeling of all types of induction generator configurations. The model makes use of rotor reference frame using a dynamic vector approach for machine model. The fuzzy logic controller is applied to the rotor side converter for active power control and voltage regulation of wind turbine. Wind turbine and its control unit are described in details. All power system components and the fuzzy controller are simulated in Matlab Simulink software. For studying the performance of the controller, different abnormal conditions are applied even the worst case. Simulation results prove the excellent performance of the fuzzy controller unit as improving power quality and stability of the wind turbine.